PENGARUH KUALITAS PELAYANAN DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA PENGGUNA TV KABEL MCN DI KOTA BATAM) - Pranoto, Emelina; Heryenzus, Heryenzus (SCIENTIA JOURNAL, 2019)
Today many companies are very aware of the importance of consumer loyalty to a product or service produced by the company. Customer loyalty will occur when satisfaction arises for a product or service. Service quality and satisfaction are very important for customer loyalty. Theepurposeeofethisestudyeisetoedetermine whether serviceequalityeand satisfaction affect theeloyalty of MCN Cable TV customers in Batam City. This study uses multiple linear regression analysis, T test to determine the effect partially, F test to determine the effect simultaneously and test the coefficient of determination R2 to find out how strong the influence of independent variables on the dependent variable and by using data collection techniques that are purposive sampling with a total 144 respondents. By using the SPSS version 20. software program The results of this study are: service quality significantly affects customereloyalty. Satisfactionehaseaesignificanteeffecteonecustomer loyalty. Serviceequalityeand satisfactionesimultaneously haveea significanteeffecteon employeeeperformance.